Annual Plan, 1995-96 Orissa Vol. II - Planning Commission (Planning Commission, 1995)
GN Statement Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98-Proposed Outlays, Physical Targets and Achievements, Draft Ninth Plan (1997-2002) Proposals for Spillover & Ongoing Programmes/Projects As In Annexure-I, Draft Ninth Plan (1997-2002) Proposals for Maximising Benefits of Completed Programme(S)Projects, Draft Ninth Plan (1997-2002) - Proposals for Programmes/Projects - New Schemes, Summary Statement Draft Ninth Plan (1997-2002) - Proposals for Programmes/Projects, Statement Regarding Externally Aided Projects, Draft Ninth Plan(1997-2002) and Draft Annual Plan 1997-98-Outlays-By Heads of Development-For District Plans, Centrally Sponsored Schemes, Draft Ninth Plan (1997-2002) and Annual Plan -1997-98 Basic Minimum Services - Outlay/Expenditure, Tribal Sub Plan (T.S.P.-I) Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 Financial Outlays Proposals for T.S.P., Tribal Sub-Plan (T.S.P.)-II Ninth Plan-1997-2002 and Draft Annual Plan-1997-98-Physical Target, Proposals for TSP, Special Component Plan for Scheduled Castes SCP-I Draft Ninth Plan -1997-2002 and Draft Annual Plan 1997-98-Financial Outlays Proposed for SCP, Special Component Plan for Scheduled Castes(S.C.P.)-II Draft Ninth Plan-1997-2002 and Draft Annual Plan 1997-98-Physical Targets, Proposals for SSP, Draft Ninth Plan(1997-2002) and Annual Plan-1997-98-Proposed Outlays Financial Outlays/Expenditure for Voluntary Sector, Women Component(WC) In the State Plan Programmes-I Draft Ninth Plan(1997-2002) and Annual Plan 1997-98 Financial Outlays for Women Component, Women Component(WC) In the State Plan Programmes-II Draft Ninth Plan(1997-2002) and Annual Plan-1997-98 Physical Targets : Proposals for Women Components.
Government of Orissa, Planning and Co-ordination Department